(untitled) (Research, Society and Development, 2020)
This article intends to investigate the possible relations between the literary product and the social universe using as basis the work O Cemitério dos Vivos, by the carioca author Lima Barreto. In order to do so, it is necessary that a new approach takes place on the properties that involve the Literature category and also the category society and at what point these two points unite and contribute to the elaboration of the aesthetic product represented by the literary work. To substantiate this article, we used the theoretical contribution defended by Candido (2006), whose approach about the relationship between literature and society is essential for the objective here intended. We also approach Schwarcz (2017) and Kilomba (2019), whose perspectives marked by the social perspective of man were addressed with emphasis in this article. The work of the writer Lima Barreto delimited here presents aspects very close to the social context surrounding this author, which provides a more detailed approach to this relationship. Thus, this article tried to show, through content analysis, and to a lesser formal degree, the support where such categories, literature and social scope are found in the work O Cemitério dos Vivos. In the conclusion of this study, it was verified that the relationship between the writer Lima Barreto and the social environment to which he belongs is determinant for the materialization of both exterior and interior nuances, thus exposing the link between the subjective element (I) and the exterior element (represented by society).